Polypharmacy and potential inappropriate drug use in the elderly admitted to the general internal medicine outpatient clinic - Celaleddin Demircan; Ulviyya Hasanzade (Turkish Journal of Internal Medicine, 2021)
In this study, we aimed to investigate the rates of polypharmacy and potentially inappropriate drug (PID) use in elderly patients who admitted to General Internal Medicine Outpatient Clinic. In this prospective cross-sectional study, the frequency of chronic diseases, the number of drugs used and polypharmacy rates of elderly patients were determined. Then, PIDs rates were investigated according to the 2015 Beers criteria. 304 (58,9% female, 41,1% male) patients were included in the study. 95,8% had at least one concomitant chronic disease, the mean number of drugs used by the patients per day was 4,9 ± 3,3 and the rate of polypharmacy was 52,9%. A total of 124 PIDs were determined in 104 (34,2%) patients, and this rate was higher in patients with polypharmacy (p < 0,05). The most common PIDs; the use of drugs that should be avoided in the elderly (Table 2-related PIDs; 28,3%), and the most common of these was the inappropriate use of proton pump inhibitors (PPIs).